Modeling the Preferences of Demographical Reading History: A Primary Case Study of a Public Library in Shanghai. Issue 1 (13th October 2021) - Lou, Wen; Chen, Jingjing
Abstract: Reading habits are influenced by various aspects, such as personal characteristics, reading history and book characteristics. It remains uncertain that which factor determines reader's choice. In this primary work, we attempt to model the preferences based on readers' demographical information to examine the impact factors on their reading habits. We selected all the reading information of Shanghai Pudong Library in 2015 as the dataset. By applying the logistical regression and likelihood ratio tests, we found that readers' stickiness, gender, and books' publication time significantly influence readers' preferences. Future work will focus on facilitating the model and expanding the data.